Medication-related Osteonecrosis of the Jaws (MRONJ), a literature review about professional knowledge and guidance given to patients to reduce risk (Research, Society and Development, 2022)
Medication-related osteonecrosis of the jaws (MRONJ), is a complication that can occur in the maxillofacial region due to the use of antiresorptive and antiangiogenic medications, which negatively affects the patient's quality of life. Adequate knowledge on the part of health professionals involved in the care of this patient, especially physicians and dentists, regarding this complication is essential for the identification of patients “at risk” and, consequently, for the control of predisposing factors and for adequate guidance and management of this complication. patient. The objective of this study was to understand the influence of professionals' knowledge about the ONMM and the guidance given to patients to reduce its risk. Methodology: This is a narrative review of the literature with an exploratory character and qualitative descriptive analysis., carried out in the VHL and Pubmed databases and using descriptors indexed in DeCs. Results: Several studies pointed out the insufficient knowledge of health professionals. Most of the studies used questionnaires and were aimed at medical professionals, dentists, pharmacists and nurses. Conclusion: The knowledge of professionals is essential to pass information and guidance to the patient and directly influences the incidence of ONMM. Adopting preventive measures, therefore, is essential for the management of Osteonecrosis.